THE STATION ROTATION METHODOLOGY: CASE STUDY IN A RURAL MUNICIPAL SCHOOL IN THE MUNICIPALITY OF VIANÓPOLIS, GOIÁS - LIMITS AND POSSIBILITIES - Jeane Freire Pereira, Magaly; Eterna Meneses Dias, Suzelita (Revista Gênero e Interdisciplinaridade, 2024)
The active methodologies to ensure teaching learning, are pedagogical approaches that seek to involve students actively in the learning process, promoting the construction of knowledge in a more significant and participatory way. The active methodology by revolutions consists of a learning approach in which students are divided into small groups and work in stations of different activities. Each station usually contains a specific task or design for students to perform within a certain period of time. After this period, students move to the next season and so on, until they have passed all the stations. The research was conducted with a 7th grade class of elementary school from a municipal school located in the rural area of ​​Vianópolis, Goiás. The data collection was due to the observation of the students during the activities and a questionnaire that they answered after the application of methodology. The results indicate that the use of this methodology promotes a stimulus to discussion, creation and reflection on the content addressed, making the students protagonists of their learning. The activity allowed students to work independently and collaboratively, exploring different themes, skills and aspects of content. In addition, it promoted students' active engagement and learning autonomy. Attitudes such as providing listening to students, valuing their opinions, exercising empathy, answering questions, encouraging them, among others, were observed and favoring the creation of a favorable environment for teaching learning. The structure of the Station Methodology by rotation is flexible and should be adapted according to the learning needs and objectives of each discipline and class. The important thing is that students have the opportunity to actively interact with content and develop collaborative, reflective and criticism